A Prospective Clinical Study to Evaluate Recurrence and Infection in Laparoscopic Hernia in a Tribal Area - Gode Dilip1 , Minaxi Yeola2 , Lamture Y.R.3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Safe surgical service is mostly inaccessible to most of the poor tribal population of theGadchiroli district of Maharashtra. Temporary multidisciplinary surgery camps can be the answer, but itssafety and cost-effectiveness were always questioned.Method: This is a prospective interventional study included 172 laparoscopic ally operated cases of inguinalhernia at Hemalkasa camp from 2015 up to 2020. Along with a study of clinical parameters like demography,infection and recurrence were evaluated.Results: Most of cases in an age group of 20- 40 years and belong to the male gender with a presentationas indirect inguinal hernia. The right side was outnumbered than left. Mesh was not fixed and a single doseof antibiotic prophylaxis was administered. A promising zero infection rate was observed with recurrencewas only in 4(2.3%) cases. Most of the patients were operated by the TEP method. Clinical presentation wasreducible swelling in groin in maximum patients. The average operative time was 60 minutes. There wereno intraoperative (neurovascular, visceral) and any post-operative complications. 4 days early return to worktime was noted with very high acceptability laparoscopic surgery in tribals was observed.Conclusions: Laparoscopic hernia repair in tibal people in multi diagnostic camps is found to have acceptableand good results. It is a safe as having zero infection and minimal recurrence rate. This procedure is alsohaving less postoperative pain and discomfort, cosmetically good with early return.